Energetic nitrocellulose coating: effective way to decrease sensitivity and modify surface property of HMX particles. Issue 2 (3rd April 2019) - Zhang, Ya-Jun; Bai, Yang; Li, Ji-Zhen; Fu, Xiao-Long; Yang, Yan-Jing; Tang, Qiu-Fan
ABSTRACT: Modifying the surface properties of energetic materials has theoretical and practical significance in the field of their application. In this paper, irregular cyclotetramethylene tetranitramine (HMX) particles were successfully coated by energetic nitrocellulose (NC), leading to the uniform NC-coated HMX particles. As coating materials, energetic (NC was chosen to decrease the sensitivity and modify the surface property of HMX particles, in order to expand their application furthermore. Scanning electron microscopy, laser particle size analysis, energy dispersive spectrometer, and Fourier-transform infrared (FT-IR) spectra were utilized to investigate the morphology, size, and coating quality of NC-coated HMX particles. These results indicated the effective preparation of composites structure. Moreover, the thermal behaviors of NC-coated HMX particles were investigated by simultaneous thermogravimetric and differential scanning calorimetry analysis, coupled with FT-IR and mass spectroscopy. These results showed that NC did not induce chemical properties change of HMX, only physical hydrogen bond was formed in the coating process. Finally, the friction sensitivity, impact sensitivity, and surface properties NC-coated HMX were investigated, and the results suggested that NC-coated HMX particles had better safety and depicted stronger interaction with the binder matrix than original HMX, owing to the stability of NC on the outer layer.